2011
DOI: 10.4103/2229-3485.86879
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes: A new era in clinical research

Abstract: Now-a-days there is significant discussion about patient-reported outcomes (PRO) in medical world. The following article covers almost all the areas of PRO including-their importance, important concepts for understanding of PRO, significance, ideal properties, types, development and evaluation of PRO instruments. It is useful for physicians, pharmacists and patients for the assessment and improvement of the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
500
1
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(517 citation statements)
references
References 12 publications
1
500
1
15
Order By: Relevance
“…9 Forest plots of effect sizes using random effect models for self-reported everyday function Edwards et al 2002;Edwards et al 2005a, b;Roenker et al 2003). Furthermore, increasing importance is being placed on patient-reported outcomes (Deshpande et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…9 Forest plots of effect sizes using random effect models for self-reported everyday function Edwards et al 2002;Edwards et al 2005a, b;Roenker et al 2003). Furthermore, increasing importance is being placed on patient-reported outcomes (Deshpande et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PRO data may enable early detection of side effects, leading to an improvement in HRQOL and improvement of disease status. [3] Patient-reported outcomes data may support the acceptance of a treatment as an agent offering economic and humanistic value to patients. [3] PROs are also expected to allow the payers of healthcare expenditure (such as government or insurance agencies) to link reimbursement to the effectiveness of treatment.…”
Section: Importance Of Patient-reported Outcomesmentioning
confidence: 99%
“…[3] Patient-reported outcomes data may support the acceptance of a treatment as an agent offering economic and humanistic value to patients. [3] PROs are also expected to allow the payers of healthcare expenditure (such as government or insurance agencies) to link reimbursement to the effectiveness of treatment. [6] To summarize, a properly collected PRO data has the potential to infl uence treatment-related decisions made by physicians, patients, hospital formularies, national health authorities, reimbursement agencies, and policy makers.…”
Section: Importance Of Patient-reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 P r e v i o u s s t u d i e s h a v e demonstrated that some perceived health dimensions are altered by the presence of a CC, while others do not suffer any impact, and this varies depending on the different diseases. The hypothesis of this study is that children with CCs will have a higher rate of lower scores in HRQoL than healthy children.…”
Section: Introductionmentioning
confidence: 99%